(untitled) (Medical Forum Monthly, 2024)
Objective: To find out the opinions of young orthodontic patients regarding aesthetic outcomes of prosthetic replacement of missing maxillary lateral incisors in comparison with the orthodontic space closure. Study Design: Cross-sectional study. Place and Duration of Study: This study was conducted at the Orthodontics department and Prosthodontics department of de ’Mont Dental College, Lahore, Pakistan, from June 2018 to June 2019. Materials and Methods: After selection of 10 intraoral photographs (5 prosthetic replacement images, 5 orthodontic space closure images) by 4 experts (2 orthodontists and 2 prosthodontics), images were presented to 100 young orthodontic patients for judgments of aesthetic outcome. Initially patients were asked to evaluate the attractiveness of 10 randomly arranged isolated photographs. Following this, 5 prosthetic replacement images were paired with 5 orthodontic space closure images, and patients were asked to evaluate these paired photographs by asking them to choose which of the two photographs they preferred. Results: The proportions of answers that reported the photographs attractive or very attractive were higher for orthodontic space closure photographs. The mean scores for orthodontic space closure photographs were high and difference between the mean scores for both sets of photographs was statistically significant. On most of the occasions while evaluating paired photographs, the patients reported a preference for the orthodontic space closure photographs. Conclusion: Orthodontic space closure was reported to be more attractive than prosthetic replacement images by young orthodontic patients and most of the patients preferred orthodontic space closure images compared with prosthetic replacement for missing maxillary lateral incisors.